Hypomorphic Mutations in the BCR Signalosome Lead to Selective Immunoglobulin M Deficiency and Impaired B-cell Homeostasis - Geier, Christoph B.; Sauerwein, Kai M. T.; Leiss-Piller, Alexander; Zmek, Isabella; Fischer, Michael B.; Eibl, Martha M.; Wolf, Hermann M. (Frontiers in Immunology, 2018)
B cell activation via the BCR signalosome involves participation of signaling molecules such as BTK and BLNK. Genetic defects in these molecules are known to impair B cell differentiation and subsequently lead to agammaglobulinemia. Here we identified novel mutations in BTK and BLNK in two unrelated patients that perturb the intrinsic B-cell receptor signaling pathway and lead to selective IgM deficiency, whereas production of other immunoglobulin isotypes and IgG antibody response remain intact. Currently it is unknown how BCR signaling strength affects mature B cell development in humans. Both patients show reduced levels of BCR signalosome phosphorylation as well as impaired BCR-dependent Ca2+ influx, which was accompanied by a marked decreased in IgD+IgM+CD27+ MZ-like B-cells. We further describe reduced expression of essential B cell differentiation factors such as BAFF-R and T-Bet in the patients’ B-cells, which might contribute to the observed deficiency of MZ-like B cells. MZ-like B cells are known to produce natural IgM antibodies that play an essential role in immune homeostasis. By using surface plasmon resonance (SPR) technology and a synthetic blood group A trisaccharide as antigen we were able to show that both patients lack the presence of anti-blood group A IgM considered to be prototypical natural antibodies whereas IgG levels were normal. Antibody binding dynamics and binding affinity of anti-blood group A IgG were comparable between patients and healthy controls. These results indicate that human IgM deficiency can be associated with signaling defects in the BCR signalosome, defective production of natural IgM antibodies in the blood group A/B/0 system and abnormalities in B cell development.